The Little REDD+ book an updated guide to governmental and non-governmental proposals for reducing emissions from deforestation and degradation - Parker, Charlie; Global Canopy Programme (Oxford, [Eng.] Global Canopy Programme, 2009)
Updated guide to governmental and non-governmental proposals for reducing emissions from deforestation and degradation.
Cover title.
Includes bibliographical references (p. 130)
Keywords: Deforestation; Forest conservation; Forest policy; Forest and forestry